Statins impact primary embryonic mouse neural stem cell survival, cell death, and fate through distinct mechanisms. - Ross A Carson; Anthony C Rudine; Serena J Tally; Alexis L Franks; Krystle A Frahm; Jacob K Waldman; Neerupma Silswal; Suban Burale; James V Phan; Uma R Chandran; A Paula Monaghan; Donald B DeFranco (PLoS ONE, 2018)
Statins inhibit HMG-CoA reductase, the rate-limiting enzyme in the cholesterol biosynthesis pathway (CBP), and are used for the prevention of cardiovascular disease. The anti-inflammatory effects of statins may also provide therapeutic benefits and have led to their use in clinical trials for preeclampsia, a pregnancy-associated inflammatory condition, despite their current classification as category X (i.e. contraindicated during pregnancy). In the developing neocortex, products of the CBP play essential roles in proliferation and differentiation of neural stem-progenitor cells (NSPCs). To understand how statins could impact the developing brain, we studied effects of pravastatin and simvastatin on primary embryonic NSPC survival, proliferation, global transcription, and cell fate in vitro. We found that statins dose dependently decrease NSPC expansion by promoting cell death and autophagy of NSPCs progressing through the G1 phase of the cell cycle. Genome-wide transcriptome analysis demonstrates an increase in expression of CBP genes following pravastatin treatment, through activation of the SREBP2 transcription factor. Co-treatment with farnesyl pyrophosphate (FPP), a CBP metabolite downstream of HMG-CoA reductase, reduces SREBP2 activation and pravastatin-induced PARP cleavage. Finally, pravastatin and simvastatin differentially alter NSPC cell fate and mRNA expression during differentiation, through a non-CBP dependent pathway.